Left Ventricular Torsion Associated With Aortic Stiffness in Hypertension. Issue 5 (28th February 2018) - Gnakamene, Jean‐Barthelemy; Safar, Michel E.; Levy, Bernard I.; Escoubet, Brigitte
Abstract : Background: Left ventricular (LV) torsion plays a key role in cardiac efficiency. In hypertension, aortic stiffening augments cardiac afterload. However, little is known about the links between LV regional contraction and aortic stiffness. We, therefore, investigated these relationships and their contribution to LV diastolic function. Methods and Results: The study included normotensive and hypertensive individuals with normal LV ejection. Apical, basal, and global LV rotation rate and LV global longitudinal strain were measured (2‐dimensional speckle tracking echocardiography). Aortic stiffness was calculated from carotid‐femoral pulse wave velocity, and LV relaxation was calculated from early diastolic mitral annulus motion. The ratio of basal or apical untwist/twist rates was calculated to assess relationships between aortic stiffness and LV torsion parameters. LV twist and untwist rates were greater in hypertensive than normotensive individuals because of increased basal twist ( P <0.001) and untwist ( P <0.001) rates. LV relaxation was reduced (early diastolic mitral annulus motion=7.4±1.9 versus 10.4±2.3 cm/s; P <0.001). In the whole population, basal untwist rate increased with aortic stiffening ( R =0.43; P <0.001) and LV relaxation ( R =0.41; P =0.001). The ratio of basal untwist/twist rate was positively correlated with carotid‐femoral pulse wave velocity, and in the hypertensive group, was greater than in the control group and positively correlated to carotid‐femoral pulse wave velocity( P <0.001). Results were independent of age, treatment, mean blood pressure, and indexed LV mass. Conclusions: In hypertensive individuals, greater basal LV torsion was associated with increased aortic stiffness and improved diastolic function. These changes may compensate for the deleterious effects of aortic stiffening on LV relaxation.